Mesenchymal Stem Cell-Derived Extracellular Vesicles for the Treatment of Bronchopulmonary Dysplasia - Xi, Yufeng; Ju, Rong; Wang, Yujia (Frontiers in Pediatrics, 2022)
Bronchopulmonary dysplasia (BPD) is the most common chronic respiratory disease in premature infants. However, there is a lack of effective treatment. Mesenchymal stromal cells derived extracellular vesicles (MSC-EVs) are heterogeneous subcellular structure secreted by MSCs, which plays an important role in repairing tissue and organ injury and is the main medium for information exchange between MSCs and injured tissue and organ. Now, EVs are considered as a new way of cell-to-cell communication. Many studies have shown that EVs mainly induce regeneration and therapeutic effects in different tissues and organs through the biomolecules they carry. The surface membrane protein or loaded protein and nucleic acid molecules carried by EVs, can activate the signal transduction of target cells and regulate the biological behavior of target cells after binding and cell internalization. MSC-EVs can promote the development of pulmonary vessels and alveoli and reduce pulmonary hypertension (PH) and inflammation and play an important role in the repair of lung injury in BPD. The regeneration potential of MSC-EVs is mainly due to the regulation of cell proliferation, survival, migration, differentiation, angiogenesis, immunoregulation and anti-inflammatory. As a new type of cell-free therapy, MSC-EVs have non-immunogenic, and are small in size and go deep into most tissues. What’s more, it has good biological stability and can be modified and loaded with drugs of interest. Obviously, MSC-EVs have a good application prospect in the treatment of lung injury and BPD. However, there are still many challenges to make MSC-EVs really enter clinical application.